A novel nucleus extraction technique using a vectis in sutureless, manual, small-incision cataract surgery - Zeng, Yuan; Deng, Jiang-wen; Gao, Jian-hua (Nepalese Journal of Ophthalmology, 2014)
Introduction: In manual, tunnel-incision cataract surgery, nucleus extraction has remained a crucial issue and a challenge. It is also the period when serious complications easily occur, especially for beginners and when the nucleus is large and dense.  Objectives: To report a modified vectis technique for nucleus extraction in sutureless, manual, small-incision cataract surgery (MSICS) to improve the safety and ease of performance.Materials and methods: A novel nucleus extraction technique using a vectis in MSICS is presented. After capsulorhexis and hydrodissection, the nucleus is moved into the anterior chamber and extracted by pulling with a Sinskey hook and pressuring on the scleral bed near the posterior wound margin with an irrigating vectis. Main outcome measures: The operating time for the whole surgery and nucleus extraction, best corrected visual acuity postoperatively and complications during and after operation were recorded. Results: In a series of 1,180 eyes, the operating time for the whole surgery and nucleus extraction were 8±3.4 minutes and 5.1±4.6 seconds respectively. Among all the eyes, 88.98 % achieved a best-corrected visual acuity of 5/10 or better two months postoperatively. The complications were posterior capsule rupture (4 eyes, 0.34 %) and transient corneal edema (12 eyes, 1.02 %). Neither vitreous loss nor dislocation of the nucleus into the vitreous was noted in the whole series of the surgery. Conclusions: We found that the “scleral bed” vectis technique for nucleus extraction improved the ease of performance, safety of MSICS, and did not require expensive instrumentation.DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11708Nepal J Ophthalmol 2014; 6 (12): 140-144